Impact of a pharmacy-driven transitions-of-care program on postdischarge healthcare utilization at a national comprehensive cancer center. (15th September 2018) - Nguyen, Phuoc Anh (Anne); Enwere, Emmanuel; Gautreaux, Stefani; Lin, Heather; Tverdek, Frank; Lu, Maggie; Cao, Henry; Chase, Judy; Roux, Ryan
Abstract: Purpose: Results of a study comparing readmission rates and medication adherence measures before and after implementation of a pharmacy-led transitions-of-care (TOC) program are reported. Methods: A quasi-experimental case–control study was conducted to assess the impact of a TOC program including medication history-taking and reconciliation services, inpatient and discharge education, and 72-hour and 30-day postdischarge phone follow-up. Hospital and emergency room (ER) readmission rates were compared in cohorts of oncology patients admitted to a large teaching hospital during specified periods before TOC program implementation (the standard-of-care [SOC] group) or after program implementation (the TOC group). The primary outcome was unplanned hospital or ER readmission within 30 days after initial discharge. The secondary endpoint was first-fill medication adherence. Benefits associated with specific TOC interventions were assessed in subgroup analyses. Results: After propensity score matching, both study groups consisted of 323 patients. The SOC group had 76 patients (23.5%) and the TOC group had 74 patients (22.9%) who were readmitted to the hospital or ER within 30 days, with a significant reduction in hospital readmissions in 1 subgroup of TOC patients versus SOC controls (absolute difference, −7.6%; p = 0.0159). Conclusion: While there were no significant overall differences in readmission rates between the TOC and SOC groups, hospital readmissions were reduced in the subgroup of TOC patients who received both medication history-taking and reconciliation services and phone follow-up as TOC interventions.